Syzygium jambos(L.)Alston(Myrtaceae) control, conservation and restoration of the threatened native flora of Pitcairn Island, South Central Pacific - Smyth, Noeleen (Trinity College (Dublin, Ireland). Department of Botany, 2008)
To fully fulfil the many aspirations of plant conservation, a quantitative, practical and economic approach to the problems in hand must be taken. Modem conservation biology involves recovering lost habitat and thwarting exotic invaders, alongside single species conservation which requires some investigation into population viability and molecular genetics. In order to fulfil these aims for conservation efforts on Pitcairn Island, a logical approach was taken for this small island ecosystem, which can be used as a model for larger and more diverse islands, and fragmented landscapes on continents, which can be considered as "islands in a sea of land".
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin